Disclosure indices design: does it make a difference? - Francisco Bravo Urquiza; Maria Cristina Abad Navarro; Marco Trombetta (Revista de Contabilidad: Spanish Accounting Review, 2009)
Measurement of information disclosed by companies is a complex task. Accounting research usually relies on disclosure indices to obtain a proxy for the information disclosed by companies. However, there is no consensus about the best design for these indices. The purpose of this paper is to investigate if there are significant differences among the indices that are used in disclosure studies. Three indices that measure disclosure of forward-looking information are compared: A “quality index” of a multidimensional nature; a “scope index” designed specifically to measure the scope of information, and a “quantity index” that measures information disclosed exclusively in terms of quantity. Results of the empirical analysis indicate that although the indices are correlated, they have a big impact in the rankings of companies. Evidence against the idea of the irrelevance of the particular index chosen is provided.